SIRT1 Activation Suppresses Corneal Endothelial–Mesenchymal Transition via the TGF-β/Smad2/3 Pathway - Yi Yu; Ruilin Guo; Jie Ling; Chenjia Xu; Minglu Ma; Xiaojuan Dong; Jing Wu; Ting Huang (Current Issues in Molecular Biology)
Endothelial–mesenchymal transition (EnMT) is the transversion of endothelial cells to mesenchymal cells under certain physiological or pathological conditions. When EnMT occurs in the corneal endothelium, corneal endothelial cells (CECs) lose their normal function and thus cannot maintain corneal clarity. Studies have shown that the mechanism of EnMT in CECs involves the transforming growth factor-β (TGF-β) signaling pathway, and one of the important inhibitors of the TGF-β/Smad2/3 pathway is sirtuin-1 (SIRT1). In this study, we used a rat model of corneal endothelium injury and TGF-β1-treated human CECs to induce EnMT, aiming to explore whether SIRT1 activation inhibits corneal EnMT in vivo and in vitro. SIRT1 was activated and suppressed using resveratrol (RSV) and EX527, respectively. The endothelial markers and mesenchymal markers were measured by immunofluorescence and Western blot assays. Co-immunoprecipitation was used to detect the interaction between SIRT1 and Smad2/3. The results showed that after mechanical injury, the group treated with RSV-activated SIRT1 regained corneal transparency and recovered from edema faster than the control group. Moreover, RSV-activated SIRT1 downregulated the expression levels of alpha smooth muscle actin (α-SMA), vimentin, and Snail and upregulated the expression levels of E-cadherin and Na+/K+-ATPase both in vivo and in vitro, but these effects were reversed when SIRT1 was inhibited by EX527. SIRT1 also upregulated the expression levels of TGF-β receptor 1 and phosphorylated Smad2/3. The interaction between SIRT1 and Smad2/3 in vitro was confirmed by co-immunoprecipitation. Overall, our results indicate that SIRT1 activation inhibits corneal EnMT via the TGF-β/Smad2/3 pathway, which may be a potential therapeutic target for corneal endothelium dysfunction.